1978
DOI: 10.1104/pp.61.2.271
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ethephon, Indole Butyric Acid, and Treatment Solution pH on Rooting and on Ethylene Levels within Mung Bean Cuttings

Abstract: Light-grown mung bean (Phaseolus aureus Roxb.) cuttings were treated with buffered and nonbuffered solutions of Ethephon, indole butyric acid (IBA), and the combination of both. Ethephon treatment resulted in increased tissue ethylene levels with increasing solution pH, but had no effect on rooting. IBA treatment had no effect on tissue ethylene levels, but strongly promoted rooting. Combinations of Ethephon and IBA had no effect on rooting of mung bean cuttings beyond that obtained by IBA alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
14
0

Year Published

1980
1980
2006
2006

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 9 publications
1
14
0
Order By: Relevance
“…Results of these studies have been highly variable. For example, in experiments using applied ethylene or ethylene-generating compounds to examine adventitious rooting in mung bean, researchers showed that ethylene stimulates rooting (Robbins et al, 1983), inhibits rooting (Geneve and Heuser, 1983), or has no effect (Mudge and Swanson, 1978). Similar experiments in tomato (Lycopersicon esculentum) have shown stimulatory effects (Hitchcock and Zimmerman, 1940;Orion and Minz, 1969;Phatak et al, 1981) and inhibitory effects (Roy et al, 1972;Coleman et al, 1980).…”
mentioning
confidence: 99%
“…Results of these studies have been highly variable. For example, in experiments using applied ethylene or ethylene-generating compounds to examine adventitious rooting in mung bean, researchers showed that ethylene stimulates rooting (Robbins et al, 1983), inhibits rooting (Geneve and Heuser, 1983), or has no effect (Mudge and Swanson, 1978). Similar experiments in tomato (Lycopersicon esculentum) have shown stimulatory effects (Hitchcock and Zimmerman, 1940;Orion and Minz, 1969;Phatak et al, 1981) and inhibitory effects (Roy et al, 1972;Coleman et al, 1980).…”
mentioning
confidence: 99%
“…Although the results of these studies have been quite variable (Geneve and Heuser 1983, Johnson and Hamilton 1977, Lipecki and Selwa 1973, Swanson 1976, most indicate that ethephon either promotes rooting (Carpenter 1975, Krishnamoorthy 1971, Robbins et al 1983b, Roy et al 1972 or has no influence on it (Chong 1982, Criley and Parvin 1979, Mudge and Swanson 1978, Nell and Sanderson 1972, Samananda et al 1972, Sanderson and Patterson 1980, Schier 1975. This variable response to ethylene could be expected, as a large number of species at different stages of development have been tested under a range of experimental conditions.…”
mentioning
confidence: 99%
“…Furthermore, ethephon may have extraneous effects on rooting which make interpretation of results difficult. These effects include the acidity of unbuffered so-lutions (Reid et al 1980), the pH dependency of release rate (Mudge and Swanson 1978), and the possible influence of breakdown products on rooting results.…”
mentioning
confidence: 99%
“…The fact that ethylene may stimulate [13,28], inhibit [5,12], or be without effect on rooting [17] has caused some confusion in this research area . The possibility that auxininduced ethylene is involved in the auxinstimulated rooting has also been considered in this literature, although the conclusions differ [10,18,22] .…”
Section: Introductionmentioning
confidence: 99%